Does leg predomination affect the measurement of patellofemoral joint reaction force (PFJRF) during single leg squatting?: A reliability study - Mostamand, Javid; Bader, Dan L.; Hudson, Zoë (Journal of bodywork and movement therapies, 2012)
Although measuring patellofemoral joint reaction forces (PFJRF) may provide reliable evidence for conservative treatments to correct probable malalignment in subjects with patellofemoral pain syndrome (PFPS), it may be necessary to determine whether the inherent properties of the dominant leg influences the reliability of measuring PFJRF. The aim of the present study was to examine the effect of leg predomination on reliability testing of the PFJRF measurement during single leg squatting in healthy subjects. Using a motion analysis system and one force plate, PFJRF of 10 healthy subjects with a right dominant leg was assessed during single leg squatting. Data was collected from superficial markers taped to selected landmarks. This procedure was performed on the both right and left legs, during three separate single leg squats from a neutral position to a depth of approximately 30° of knee flexion. Subjects were then asked to repeat the test procedure after a minimum of a week’s interval. The PFJRF was calculated using a biomechanical model of the patellofemoral joint. There was significant difference between the PFJRF mean values of paired test of right (mean, SD of 1887.7, 325.1 N) and left knees (mean, SD of 2022.6, 270.5 N) (p < 0.05). The CV (coefficient of variation) values during within and between session tests, revealed the high repeatability and reproducibility of PFJRF measurements on both knees. The ICC (intra class correlation coefficient) values during within and between sessions tests showed the high reliability of these measurements on both knees. The high reliability of PFJRF measurements on both dominant and non-dominant legs of healthy subjects suggests that the PFJRF measurement would not be influenced by the leg predomination during single leg squatting.